Towards design of citizen centric e-government projects in developing country context: the design-reality gap in Uganda - Kyakulumbye, Stephen (2021)
E-government projects should be at the heart of service delivery in developing countries if the lives of citizens, especially the socially and economically marginalized, are to be improved. However, quite often in developing country contexts, citizens have been treated as recipients of technology projects through a top-down approach from central governments. Such a paradigm of implementation usually results in the non-use of the deployed technologies and their associated e-services. A consequence of non-use of e-services results in a wastage of the public fiscus. The extant literature points to a number of underlying causes of the problem. One such problem which has been highlighted is called the “Design-Reality gap”. This paper investigates the nature of the gap. It presents findings from policy analysis and in-depth face-to-face interviews with e-government policy makers and implementers. In addition, it reports on findings from focus group discussions with potential e-government users in a health sector setting. The results which are based on a participatory action research methodology reveal that there exists a glaring design-reality gap between egovernment policy planners and citizens’ aspirations. We argue that co-creation could be a feasible approach for the design of e-government application services towards efforts to bridge the design-reality gap.